Sustainable Downstream Processing of Microalgae for Industrial Application. - Gayen, Kalyan; Bhowmick, Tridib Kumar; Maity, Sunil Kumar (Boca Raton : CRC Press, 2019)
Microalgae can be future resource for industrial biotechnology In current energy crisis era, microalgae are under tremendous research focus for the production of biodiesel due to their high photosynthetic efficiency, growth rate and high lipid content compared to territorial plants. However, the large-scale production of algal biomass and downstream processing of harvested algae towards bio-fuels are facing several challenges from economic viability perspective. Apart from bio-fuels, the microalgae synthesize number of bio-molecules such as pigments (e.g., chlorophyll, carotenoid), protein (e.g., lectin, phycobiliprotein), and carbohydrates (e.g., agar, carrageenan, alginate, fucodian) which are available in the various forms of microalgal products. Therefore, developing a strategy for large-scale production and use of algal biomass for the co-production of these value-added macromolecules is thus imperative for the improvement of the economics of algal biorefinery. In the above context, this book covers three major areas (i) commercial-scale production of bio-molecules from microalgae, (ii) sustainable approach for industrial-scale operation, and (iii) optimization of downstream processes. Each of these sections is composed of several chapters written by the renowned academicians/industry experts. Furthermore, in this book, a significant weightage is given to the industry experts (around 50%) to enrich the industrial perspectives. We hope that amalgamate of fundamental knowledge from academicians and applied research information from industry experts will be useful for forthcoming implementation of a sustainable integrated microalgal biorefinery. This book highlights following. Explores biomolecules from microalgae and their applications Discusses microalgae cultivations and harvesting Examines downstream processing of biomolecules Explores sustainable integrated approaches for industrial scale operations Examines purification techniques specific for microalgal proteins, Omega 3 fatty Acids, carbohydrates, and pigments
Part 1: Biomolecules from Microalgae for Commercial Production. 1. Biomolecules from Microalgae for Commercial Applications. 2. Promising Future Products from Microalgae for Commercial Applications. 3. Cultivation of Microalgae for Production of Biomolecules and Bioproducts at Industrial Scale. 4. Industrial Scope with High-Value Biomolecules from Microalgae. Part 2: Sustainable Approach for Industrial-Scale Operations. 5. Sustainable Pre-treatment Methods for Downstream Processing of Harvested Microalgae. 6. Sustainable Approach for Bioenergy and Biofuel Production from Microalgae. 7. Sustainable Production of Bioproducts from Wastewater-Grown Microalgae. 8. Integrated Approach for the Sustainable Extraction of Carbohydrates and Proteins from Microalgae. Part 3: Optimized Downstream Processing of Microalgae. 9. Current Issues with a Sustainable Approach in the Industrial-Scale Operations of Microalgae. 10. Trends and Bottlenecks of Sustainable Mitigation of Environmental IssuesUsing Microalgae. 11. Optimization of the Integrated Downstream Processing of Microalgae for Biomolecule Production.
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / General; MEDICAL / Biotechnology; SCIENCE / Biotechnology; Microalgae -- Industrial applications